A model to extend spectral and multiwavelength UV irradiances time series: Model development and validation - Diaz, Susana Beatriz; Nelson, Don; Deferrari, Guillermo Alejandro; Camilión, María Carolina (Journal of Geophysical Research)
Measurements of spectral and multichannel UV radiation became more common in the middle and late eighties after the discovery of the ‘‘ozone hole,’’ but time series for these measurements are still relatively short for the determination of trends to be applied in geophysical and biological studies. However, systematic measurements of total column ozone have been performed since the late 1950s at several stations, and global coverage has been available since the late 1970s. Also, long-term time series of broadband instruments (Pyranometers, UV and erythemally weighted) are available from many sites around the world. In this paper a multiregressive model that enables the inference of spectral or narrow band UV irradiances from total ozone column and broadband irradiance, in places where relatively short time series of UV spectral irradiances are available, is proposed. To test the model, measurements of irradiances performed at three of the stations in the NSF UV Radiation Monitoring Network, under all weather, solar zenith angle and surface conditions, were used. The model generated very good results over a wide variety of situations. Pyranometer data from the NOAA/CMDL surface radiation budget database for South Pole and Barrow Stations were used to estimate daily integrated narrow band irradiances. A time series of monthly means for the narrowband (303.030–307.692 nm) were then computed, dating back to the late 1970s. INDEXINDEX TERMS: 1630 Global Change: Impact phenomena; 1694 Global Change: Instruments and techniques; 3309 Meteorology and Atmospheric Dynamics: Climatology (1620); KEYWORDS: UV-B Irradiances, Ozone, Ozone depletion, UV irradiance modeling, Multiregressive modelERMS: 1630 Global Change: Impact phenomena; 1694 Global Change: Instruments and techniques; 3309 Meteorology and Atmospheric Dynamics: Climatology (1620); KEYWORDS: UV-B Irradiances, Ozone, Ozone depletion, UV irradiance modeling, Multiregressive modelKEYWORDS: UV-B Irradiances, Ozone, Ozone depletion, UV irradiance modeling, ...